Pull-off adhesion of hybrid glass-steel adhesive joints in salt fog environment. Issue 19 (1st October 2016) - Fiore, V.; Calabrese, L.; Proverbio, E.; Galtieri, G.; Scalici, T.; Lo Presti, V. M.; Valenza, A.
Abstract: The aim of this paper was to evaluate the durability behaviour of glass/steel adhesive joints exposed to salt fog environmental conditions for ten weeks, according to ASTM B117 standard. To this scope, pull-off mechanical tests were carried out in order to evaluate the performances evolution and damage phenomena of the adhesive joints during the ageing exposition. Two different types of adhesives were compared (i.e. epoxy and polyurethane ones). Moreover, the effects of the glass surface condition and the presence of a basalt mat layer within the adhesive thickness were evaluated. The mechanical performances were related with the occurred failure mechanisms. Epoxy-based joints showed higher strength and durability than the polyurethane based ones. Furthermore, frosted glass surface condition and basalt interlayer addition enhanced mechanical durability in salt fog environment of glass–metal dissimilar joints.